Edaphic fauna in banana production systems in the South of Santa Catarina, Brazil Fauna edáfica em sistemas de produção de banana no Sul de Santa Catarina - Casaril C.E.* (2019)
© 2019 Universidade Federal Rural de Pernambuco. All rights reserved.Soil fauna is sensitive to changes in the environment and, therefore, can be efficient as an indicator of quality in banana production areas. The objective of the study was to evaluate the effects of banana on fauna and in function of the different cultural practices, management and chemical and physical aspects of the soil. Was evaluate two banana fields and an area of native forest, in the south of Santa Catarina in two seasons. For the collection of fauna, the technique of pitfall traps and soil monolith is used and also, a chemical and physical soil was evaluated. For the fauna was evaluated the abundance and richness of organisms sampled, diversity indexes of Shannon-Wiener and Pielou and multivariate processes was done. The main groups in the collection of pitfall traps in the banana fields were Collembola, Formicidae and Acari and in the collection by the soil monolith, are Oligochaeta and Diptera (larvae) groups. Regarding diversity indexes in banana plantations, the highest indices are in the last collection by soil monolith. Identified fauna relation with pH, Al+3, Fe+3, Zn+2, Mg+, macroporosity and soil density. It is concluded, as the main cultural practices of the banana fields related with fauna are fertilization and disposal of cultural remains in the soil.